Collaborative Duality of CircGLIS3(2) RNA and Protein in human Wound Repair - Guanglin Niu; Maria A. Toma; Jennifer Geara; Xiaowei Bian; Yongjian Chen; Lihua Luo; Qizhang Wang; Yunting Xiao; Manika Vij; Minna Piipponen; Zhuang Liu; Sho Oasa; et al. (Advanced Science, 2025)
Abstract The discovery of an increasing number of translatable circular RNAs (circRNAs) raises the question of whether their coding and non‐coding functions can coexist within the same cell. This study profiles the dynamic expression of circRNAs during human skin wound healing. CircGLIS3(2) is identified, a circRNA whose levels transiently rise in dermal fibroblasts of acute wounds and are abnormally overexpressed in keloids, a fibrotic skin condition. Injury signals such as IL‐1α, TGF‐β, hypoxia, and ER stress induce both expression and cap‐independent translation of CircGLIS3(2). The RNA form of CircGLIS3(2) activates fibroblasts into matrix‐secreting cells, while its encoded protein promotes cell proliferation, collectively enhancing wound repair. Mechanistically, CircGLIS3(2) RNA stabilizes the cytoplasmic protein PCOLCE, while its protein binds to BTF3 in the nucleus. Both the RNA and protein are essential for wound closure in human and murine models. CircGLIS3(2)’s bifunctional nature expands its functional spectrum, improving cellular adaptability during environmental changes and offering a promising therapeutic target for wound repair and scar reduction.